2023
DOI: 10.33003/fjs-2023-0701-1168
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metals by Adsorbent Produced From Khaya Senegalensis

Abstract: Mankind quest for better life has led to advancements in modern technologies which include a number of manufacturing processes and methodologies. Some of these processes and methodologies often release harmful substances into the environment including heavy metals which lead to pollution. These heavy metals are non-biodegradable and therefore need to be removed. Attention has been devoted to emerging technologies which are relatively cheap, for the removal of heavy metal ions from contaminated waters. Adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[4]. Heavy metals, such as Pb, Cd, and Hg [5][6][7], are hazardous and persistent contaminants that can accumulate in aquatic environments, posing a major danger to biodiversity and water quality [8]. To address this important issue, the development of efficient and cost-effective water treatment technology is critical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4]. Heavy metals, such as Pb, Cd, and Hg [5][6][7], are hazardous and persistent contaminants that can accumulate in aquatic environments, posing a major danger to biodiversity and water quality [8]. To address this important issue, the development of efficient and cost-effective water treatment technology is critical.…”
Section: Introductionmentioning
confidence: 99%
“…In pursuit of these objectives, we will conduct a series of controlled experiments, systematically varying the influential factors such as contact time, adsorbent dosage, and initial metal ion concentration, as exemplified in previously related study using banana stalk biosorbent demonstrated using central composite design (CCD) response surface methodology (RSM) [21]. Temperature and pH as tested on zinc, cadmium, chromium and nickel removal from water by Adamu (2023), are additional factors affecting the process. In addition, natural water embraces several competitive ions that might contend with the adsorbate for a few numbers of active sorption sites, upsetting the sorption capacity of the biosorbent.…”
Section: Introductionmentioning
confidence: 99%